Roughness Effects on Continuous and Discrete Flows in Superhydrophobic Microchannels (Communications in Computational Physics, 2020)
The dynamic behaviors of continuous and discrete flows in superhydrophobicmicrochannels are investigated with a lattice Boltzmann model. Typical charactersof the superhydrophobic phenomenon are well observed from our simulations, includingair trapped in the surface microstructures, high contact angles, low contactangle hysteresis, and reduced friction to fluid motions. Increasing the roughness ofa hydrophobic surface can produce a large flow rate through the channel due to thetrapped air, implying less friction or large apparent slip. The apparent slip length appearsto be independent to the channel width and could be considered as a surfaceproperty. For a moving droplet, its behavior is affected by the surface roughness fromtwo aspects: the contact angle difference between its two ends and the surface-liquidinterfacial friction. As a consequence, the resulting droplet velocity changes with thesurface roughness as firstly decreasing and then increasing. Simulation results are alsocompared with experimental observations and better agreement has been obtainedthan that from other numerical method. The information from this study could bevaluable for microfluidic systems.